General engineering knowledge : for marine engineers - Russell, Paula; Jackson, Leslie; Morton, Thomas D. (Adlard Coles Nautical, 2013)
Developed to complement Reeds Vol. 12 (Motor Engineering for Marine Engineers), this textbook is key for all marine engineering officer cadets. This new edition has been extensively updated to include the latest equipment, practices and trends in marine engineering, as well as incorporating the 2010 Manila Amendments, particularly relating to Management. Accessibly written and clearly illustrated, this book is the core guide focusing on the knowledge needed for passing the engineering certificate of Competency (CoC) examinations. This key textbook takes into account the varying needs of studen.
Includes index.
Keywords: Marine engineering.; Marine machinery.; elektronické knihy; electronic books